KETERKAITAN ANTARA SARANA DAN PRASARANA DENGAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Ananda, Rizki; Meiwati, Lutfia; Lestari, Yessi; Anum, Fatma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to examine the relationship between educational facilities and infrastructure and the quality of learning in elementary schools. The availability of educational resources such as classrooms, libraries, laboratories, learning media, and other resources is increasingly important in creating a conducive learning environment and increasing student motivation and achievement. This study uses a literature study method by analyzing several academic sources, including journals, books, and documents related to education. The results of the study indicate a positive and significant relationship between facilities and infrastructure and the learning community. Effective teaching methods, consistent instruction, and the use of educational media and technology can all contribute to a more effective and engaging learning process. These findings highlight the need for improving educational standards in effective management and active involvement of educators and the community to improve the quality of elementary education.Keywords: facilities and infrastructure, learning quality, elementary school, educational management, learning motivation